Dilema Keadilan Fiskal Berbasis Utilitarianisme Terhadap Penolakan Alokasi APBN Dalam Penyelesaian Utang Infrastruktur Kereta Cepat - Ahsan, Muh Akmal; Safitri, Sena Putri (Fakultas Hukum Universitas Primagraha, 2025)
The construction of the Jakarta-Bandung High-Speed Railway (KCJB) project has created a fiscal justice dilemma when cost overruns led to a proposal to use the State Budget (APBN) to cover the debts of the corporation PT Kereta Cepat Indonesia China (KCIC). This study uses a normative legal method with a conceptual and philosophical approach, combining utilitarianism theory (Act and Rule Utilitarianism) with state financial principles based on Articles 23 and 23A of the 1945 Constitution. Data was collected through secondary sources, including legal documents, as well as official documents such as the Central Government Financial Report, Presidential Regulations on National Strategic Projects, and BPK audit reports and related academic literature. The analysis was conducted qualitatively with systematic and teleological interpretations to assess the suitability of APBN usage practices with the principles of fiscal justice and utilitarianism theory (both Act and Rule Utilitarianism). The results of the study show that the use of the state budget to bail out corporate debt has the potential to create fiscal moral hazard, obscure the principle of separation of state assets, and undermine public trust in the taxation system. Conversely, the rejection of state budget allocations reflects the application of Rule Utilitarianism, which maintains fiscal legal integrity, budgetary discipline, and fairness in the distribution of the tax burden. This research contributes to the development of the concept of “constitutional utilitarianism,” which is a legal ethical framework that balances economic benefits with the principle of fiscal justice in state financial management. It also provides legislators with a framework for designing oversight mechanisms for national strategic projects so as not to violate the principle of a welfare state.